Orai1 promotes tumor progression by enhancing cancer stemness via NFAT signaling in oral/oropharyngeal squamous cell carcinoma - Sung Hee Lee; Nicole Kristina Rigas; Chang-Ryul Lee; April Bang; Sonal Srikanth; Yousang Gwack; Mo Kang; Reuben H. Kim; No‐Hee Park; Kihyuk Shin (2016)
// Sung Hee Lee 1 , Nicole Kristina Rigas 1 , Chang-Ryul Lee 1 , April Bang 1 , Sonal Srikanth 2 , Yousang Gwack 2 , Mo K. Kang 1,3 , Reuben H. Kim 1,3 , No-Hee Park 1,3,4 and Ki-Hyuk Shin 1,3 1 The Shapiro Family Laboratory of Viral Oncology and Aging Research, UCLA School of Dentistry, Los Angeles, CA, USA 2 Department of Physiology, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA 3 UCLA Jonsson Comprehensive Cancer Center, Los Angeles, CA, USA 4 Department of Medicine, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA Correspondence to: Ki-Hyuk Shin, email: // Keywords : Orai1, OSCC, cancer stem cells, NFAT, SOCE Received : May 20, 2016 Accepted : May 26, 2016 Published : June 01, 2016 Abstract Emerging evidence indicates that Orai1, a key calcium channel for store-operated Ca 2+ entry, is associated with human cancer. However, the underlying mechanism by which Orai1 regulates cancer progression remains unknown. Here we report that intracellular level of Orai1 is increased in a stepwise manner during oral/oropharyngeal carcinogenesis and highly expressed in cancer stem-like cell (CSC)-enriched populations of human oral/oropharyngeal squamous cell carcinoma (OSCC). Ectopic Orai1 expression converted non-tumorigenic immortalized oral epithelial cells to malignant cells that showed CSC properties, e.g., self-renewal capacity, increased ALDH1 HIGH cell population, increased key stemness transcription factors, and enhanced mobility. Conversely, inhibition of Orai1 suppressed tumorigenicity and CSC phenotype of OSCC, indicating that Orai1 could be an important element for tumorigenicity and stemness of OSCC. Mechanistically, Orai1 activates its major downstream effector molecule, NFATc3. Knockdown of NFATc3 in the Orai1-overexpressing oral epithelial cells abrogates the effect of Orai1 on CSC phenotype. Moreover, antagonist of NFAT signaling also decreases CSC phenotype, implying the functional importance of Orai1/NFAT axis in OSCC CSC regulation. Our study identifies Orai1 as a novel molecular determinant for OSCC progression by enhancing cancer stemness, suggesting that inhibition of Orai1 signaling may offer an effective therapeutic modality against OSCC.